Lack of Effect of Propranolol on the Reconsolidation of Conditioned Fear Memory due to a Failure to Engage Memory Destabilisation. (1st January 2022) - Rotondo, Federico; Biddle, Kathryn; Chen, John; Ferencik, Josh; d'Esneval, Mathilde; Milton, Amy L.
Highlights: Propranolol did not disrupt the reconsolidation of pavlovian fear memories. Varying reactivation parameters to enhance prediction error did not change outcomes. Molecular markers of destabilisation suggest that the memory did not become labile. Abstract: The prospect of exploiting memory reconsolidation to treat mental health disorders has received great research interest, particularly following demonstrations that the β-adrenergic receptor antagonist propranolol, which is safe for use in humans, can disrupt the reconsolidation of pavlovian conditioned fear memories. However, recent studies have failed to replicate the effects of propranolol on fear memory reconsolidation, and have questioned whether treatments based upon reconsolidation blockade would be robust enough for clinical translation. It remains possible, though, that studies reporting no effect of propranolol on memory reconsolidation could be due to a failure to engage the memory destabilisation process, which is necessary for the memory to become susceptible to disruption with amnestic agents. Demonstrating that memory destabilisation has not been engaged is challenging when only using behavioural measures, but there are molecular correlates of memory destabilisation that can be used to determine whether memory lability has been induced. Here, we attempted to replicate the classic finding that systemic administration of propranolol disrupts the reconsolidation of a pavlovian auditory fear memory. Following a failure to replicate, we manipulated the parameters of the memory reactivation session to enhance prediction error in an attempt to overcome the boundary conditions of reconsolidation. On finding no disruption of memory despite these manipulations, we examined the expression of the post-synaptic density protein Shank in the basolateral amygdala. Degradation of Shank has been shown to correlate with the induction of memory lability, but we found no effect on Shank expression, consistent with the lack of observed behavioural effects.